2016
DOI: 10.1097/mcg.0000000000000580
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Patients With Diverticulosis and Diverticular Disease in Primary Care

Abstract: This survey shows that the current management of DD in primary care by Italian GPs is not fully in line with current guidelines and more recent literature data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
6
0
3
Order By: Relevance
“…There is a lack of rationale for drug use, including rifaximin, for primary prevention of diverticulitis in patients with diverticulosis, and pharmacological intervention including rifaximin use should be avoided in this setting. Interestingly, a recent Italian primary care survey reported that 51% of patients with diverticulosis are treated with cyclic rifaximin for primary prevention of acute diverticulitis [90]. This surprising finding notes the important gap between evidence-based medicine and clinical practice in Italy.…”
Section: Methodsmentioning
confidence: 99%
“…There is a lack of rationale for drug use, including rifaximin, for primary prevention of diverticulitis in patients with diverticulosis, and pharmacological intervention including rifaximin use should be avoided in this setting. Interestingly, a recent Italian primary care survey reported that 51% of patients with diverticulosis are treated with cyclic rifaximin for primary prevention of acute diverticulitis [90]. This surprising finding notes the important gap between evidence-based medicine and clinical practice in Italy.…”
Section: Methodsmentioning
confidence: 99%
“…(1). In this way, several treatments tested in controlled trials seem to be effective (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Thus, these treatments may be not cost-effective in preventing acute diverticulitis occurrence/recurrence and in term of surgery prevention, but maybe effective in controlling symptoms (23).…”
Section: Discussionmentioning
confidence: 99%
“…As stated, several treatment are currently prescribed in the Italian people having diverticulosis in order to prevent acute diverticulitis occurrence/recurrence and surgery occurrence (13,14). In particular, four main treatments are currently prescribed.…”
Section: Methodsmentioning
confidence: 99%
“…44 % responderů doporučuje vlákninu, s omezením semínek u 30 %, z léků se u symptoma tické nekomplikované nemoci nejčastěji podávaly rifaxi min, probiotika a mesalazin u 82,8 %, 59,54 % a 36,3 % nemocných. Ve stejném pořadí se tyto léky podávaly v prevenci divertikulitidy [112]. Realitu širší klinické praxe také reflektuje dotazník vyplněný 115 gastroenterology a chirurgy z 8 evropských zemí.…”
Section: Divertikulární Nemoc (Dn)unclassified